Inclined slicing of a thick coal seam in ascending order — A case study - A. K. Singh; R. Singh; M. Sarkar; P. K. Mandal; D. Sharma (Canadian Institute of Mining, Metallurgy and Petroleum, 2002)
"This paper deals with the stability investigations carried out at the XIVth seam of Jitpur colliery. The study was conducted to investigate the possible causes of roof cavity formation and face spalling at the middle slice face of block-3 longwall panel and to suggest remedial measures. The instrumentation and monitoring work was carried out in the panel over a period of nine months. On the basis of observations, it was found that if the maximum face span was reduced from the existing 4.8 m to 3.6 m, and if the face time schedule cycle was reduced from a maximum of 37 days to about 18 days, this problem could be eliminated. The recommendations of CMRI have been implemented in the middle slice face of block-4 panel with success. IntroductionModerate to steeply dipping, undisturbed seams of uniform thickness are worked by way of inclined slicing parallel to walls. In this method, the seams are treated as a combination of several moderately thick seams dipping parallel to roof and floor. Numerous variations of multislice mining have been used worldwide to get high coal recovery under local conditions of geology, subsidence control, proness to spontaneous combustion, statutes and economics. Multislice mining can proceed either downward descending from the roof or upward ascending from the floor. Ascending methods require backfill behind the working face to provide a base for the next slice. It is also adopted for surface protection against subsidence or mining under a massive roof. This paper presents a scientific study conducted in Jitpur colliery, IISCO where a 9 m thick seam is mined in three slices in ascending order with stowing."